Evaluation of mohair quality in Angora goats from the Northern dry lands of Tajikistan - Kosimov, F.F. (2013)
Mohair quality of Angora goats in the Sogd Province of Tajikistan was assessed in spring and autumn 2007 and 2008 by inspecting and sampling a total of 797 goats of both sexes, different ages and several coat colors from 15 randomly selected flocks. Fiber fineness was assessed visually on the Bradford scale, staple length was measured with a ruler. Midside fleece samples were analyzed with an OFDA instrument to determine average fiber diameter, standard deviation, coefficient of variation (CVFD), comfort factor, fiber curvature and fiber length. On a subset of 153 goats, kemp and med fiber percentage were determined inspecting 300 fibers of each goat with a projection microscope. Mixed model procedures were used to analyze the data. Residuals of the model were used to calculate correlations. The random flock effect was significant for all traits and the fixed sex, age, and color effects were significant for most traits. In spring shearing data, fiber diameter of males was 2.7 μm coarser than females and increased with age: 27.3 μm (1 year old), 31.3 μm (2 years old), 34.6 μm (3–5 years old) and 37.0 μm (6 years and older). Mohair fiber length ranged 137.3–174.7 mm between ages. Six-month-old kid mohair (autumn shearing) was finest (24.4 μm) and shortest (95.1 mm). White mohair was approximately 3 μm coarser than brown and gray mohair. CVFD was not affected by sex and age but related to color with white mohair having a lower CVFD. Comfort factor and visual Bradford count decreased with age. Average med and kemp percentages were 0.88 and 0.34. Almost 20% of goats had 2% or more medullated fibers. The phenotypic correlation between fiber diameter and med percentage was 0.40 and between fiber diameter and kemp percentage −0.08. On average, visual Bradford count underestimated fiber diameter by about 4.1 μm. The correlation between fiber diameter and Bradford count was −0.28. Thus, visual assessment of fiber diameter is imprecise and reduction of fiber diameter through selection would therefore require analysis of fleece samples. The correlation between staple length and fiber length was 0.78. Thus, ruler determination of staple length measured on the live animals is a good estimator of fiber length measured on the fleece sample. In comparison with South African mohair, Tajik mohair is not only white, has long fibers, is rather coarse and medullated. Given the high variation between and within flocks in fiber diameter and medullation there is room for culling inferior animals and improve current mohair quality